SARS-COV-2 INFECTION AND SEROCONVERSION IN PEDIATRIC INFLAMMATORY BOWEL DISEASE PATIENTS. (21st January 2021) - Ruan, Wenly; Ihekweazu, Faith; Walsh, Seema; Karam, Lina; Wyatt, Allyson; Nguyen, Huyen; Kellermayer, Richard
Abstract: Background: As the Coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to evolve, its influence on specific patient populations suffering from chronic disorders becomes increasingly important. Patients with inflammatory bowel disease (IBD) are commonly immunosuppressed with immunomodulators, biologics, and steroids. Therefore, IBD patients have been considered as a risk population for COVID-19. Yet, emerging epidemiologic data may indicate otherwise. It is still unclear, however, how COVID-19 infection affects IBD patients and how seroconversion against the virus might take place depending upon disease states and treatments. We describe a single center cohort of pediatric IBD patients with COVID-19, a subset of whom were tested for seroconversion subsequent to the laboratory test supported infection. Methods and Results: The electronic medical records of pediatric IBD patients who tested positive for SARS-CoV-2 by nasopharyngeal swab based PCR testing were included in the study. The clinical course of IBD, concurrent medications, COVID-19 related symptoms, SARS-CoV-2 testing date, and SARS-CoV-2 IgG antibody testing date and result were examined. A total of 13 pediatric IBD patients at Texas Children's Hospital tested positive for SARS-CoV-2. Patient demographics and specifics of IBD disease and management are detailed in table 1. Management was not altered in any of these patients in response to the positive COVID-19 test. Seven (53.8%) had symptoms including fever, sore throat, fatigue, loss of taste, dizziness, loss of smell, abdominal pain, and/or diarrhea; six (46.2%) were asymptomatic. No patients required hospitalization attributed to COVID-19. Of the 13 patients, 6 (46.2%) have been already tested for seroconversion. Four (67.7%) had elevated SARS-CoV-2 IgG of whom 3 patients (50%) had acute and resolved symptoms; one (16.7%) had an ambiguous serology (reactive total IgG and IgM but negative IgG and IgM individually), and one (16.7%) had nonreactive antibody titers. Seroconversion was tested between 0.4, or 4 to 13.7 weeks after initial positive SARS-CoV-2 PCR testing. The close antibody testing at 0.4 weeks had the ambiguous results. Serologic testing for the additional cases is pending. Conclusions: We describe a cohort of pediatric IBD patients with COVID-19 ranging from 1 week to 4 months after infection whose disease course has not been significantly affected. A large proportion of patients tested for seroconversion were found to mount a detectable IgG based immune response in spite of their medical immunosuppression. More research needs to be performed to evaluate the importance of seroconversion with relation to disease course andCOVID-19 reinfection in pediatric IBD patients.